Регіональні інтернет-ЗМІ: харківський і львівський досвід - Коцарев, О.О. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2007)
Статья посвящена анализу структуры двух интернет-СМИ: харьковской интернет-газеты «МедиаПорт» и львовской «КуПол». По результатам исследования автор достаточно высоко оценивает профессионализм этих СМИ, однако считает необходимым устранение таких недостатков, как недостаточное использование возможностей интерактивности интернет-газетой «КуПол» и узкую жанровую палитру и небольшую вместимость файлов «МедиаПорта». The aim of the paper is to analyse the structure of two internet-media: the internet-newspaper MediaPort of Kharkiv and the internet-newspaper CuPol of Lviv. As a result the author gives an appreciation to professional level of these media. But he insists on elimination of defects such as not adequately using of the interactivity in the CuPol, limited paradigm of the genres and to little capacity of the files in the MediaPort.
Keywords: інтернет-ЗМІ; інтернет-журналістика в Україні; «МедіаПорт»; «КуПол»